REPRESENTASI PEREMPUAN SEBAGAI SUB-ALTERN DALAM FILM GOWOK KAMASUTRA JAWA - M Kurniawan Putra, Rivaldy, Taufik Mulyanto P. (PT Wahana Global Education, 2025)
This study analyzes the representation of women as subalterns in the film Gowok Kamasutra Jawa directed by Hanung Bramantyo, employing Gayatri Spivak’s subaltern theory and a critical discourse analysis approach. The tradition of gowok, which historically serves to prepare prospective grooms with knowledge of household life and sexuality, is often reduced in films and media to mere objects of sensuality and moral controversy. This study finds that media and cinematic narratives emphasize erotic and sensational aspects, thereby marginalizing the agency and experiences of women. The visualization of female bodies, the symbolism of traditional attire, as well as the dialogues and gestures of women in the film, reinforce their position as subalterns who lack the epistemic space to articulate their own voices and interests. The unequal power relations between gowok and the prospective grooms further consolidate patriarchal dominance, where women are present solely as facilitators of male needs. These findings underscore the necessity of reframing women's narratives in culture and media to provide authentic spaces for articulating women’s voices and experiences.